(untitled) (Orfeu, 2025)
Olivier Messiaen (1908-1992) composed Et exspecto resurrectionem mortuorum for winds orchestra and metallic percussion in 1964. The piece has five movements of hieratic and monumental, static and ecstatic character, and yet, of great formal simplicity. This study is an analysis concerned with how this simplicity is constructed by means of a compositional principle that is common to the five movements, the intention of each being to produce in the listener an experience of the sacred through sound. This, the sound, is presented in a practically absolute way both as silence and as a glorious and splendid sound potency.